IMPROVING STUDENTS READING COMPREHENSION ON RECOUNT TEXT THROUGH QUESTION ANSWER RELATIONSHIP STRATEGY (QAR) - Utami, Nurul Puteri; Regina, Regina; Rosnija, Eni (FKIP - Universitas Tanjungpura, 2020)
This research aims to improve students reading comprehension on recounttext by using Question Answer Relationship (QAR) strategy. This researchis a classroom action research which was conducted in three cycles. Theparticipants of this research consist of the teacher and the students in classX IIS 3 of SMAN 1 Sungai Raya. The researcher collected the data ofstudents improvement in reading comprehension by observing the datathrough reading test, observation checklist, field note and self-assessmentforms. The result showed that students problems in comprehending recounttext had been solved by using QAR strategy. Right There and Think andSearch question improved students understanding of generic structure andlanguage features of recount text. The mean score of students readingcomprehension enhanced in each cycle. In the first cycle, the students meanscore was 57.2, it increased to 68.8 in the second cycle, and 82 in the thirdcycle. In other words, Question Answer Relationship (QAR) strategyimproved students reading comprehension of recount text.